Modern assistive and augmentative technologies supporting communication, education and social functioning of individuals with hearing impairment - Małgorzata Kupisiewicz; Paulina Zagrobelna (Studia z Teorii Wychowania)
Hearing disability and its consequences are approached taking into consideration two viewpoints: medical-rehabilitative that exposes a hearing deficit and limitations of access to the world of sounds, including speech and communication in phonic language; and sociocultural that does not perceive deafness as disability but as a positive value in the Community of the Deaf – people who qualify as a linguistic and cultural minority that communicate using sign language. Currently, at the time of intense development of new technologies, new prospects and opportunities are created that change the face of hearing disability and the Deaf Community. This article attempts to show selected modern assistive technologies and how they might affect improvement of the quality of life of hearing impaired and deaf/Deaf individuals. The focus of the article is on demonstrating the importance of the functional assistive devices and other technologies as strategies of mitigating, preventing or compensating the difficulties related to interpersonal and social communication, increasing access to education and public space for people with hearing impairment and also enhancing their ability to participate in social life independently and unassisted.Key words: hard-of-hearing individuals, deaf/Deaf individuals, assistive technologies, quality of life